Pengaruh Jarak Tanam dan Takaran Pupuk Kandang Sapi terhadap Pertumbuhan dan Hasil Tanaman Buncis (Phaseolus vulgaris L.) - Reni Marianti Missa (Fakultas Pertanian, Universitas Timor, 2018)
This study aims to determine the effect of spacing and dosage of manure on the growth and yield of chickpeas and to determine the dosage of manure and the appropriate spacing for growth and optimum bean yield. The design used was factorial randomized block design (RBD) 3 x 3 which was repeated three times. The first factor is the spacing consisting of three levels, namely 20 cm x 40 cm, 20 x 50 cm and 20 cm x 60 cm. the second factor is the dose of manure consisting of three levels, namely 5 t / ha, 10 t / ha and 15 t / ha. Parameters observed included soil temperature, soil moisture content, plant height, stem diameter, number of leaves, number of pods per plant, pod weight per plant, number of pods per plot, weighted wet weight, dry dry weight, root wet weight, dry weight root, stem wet weight, stem dry weight. The results showed that the interaction between spacing and dosage of cow manure occurred in the parameters of root wet weight and number of pods per plot per harvest. The dosage of manure has a significant effect on moisture content parameters of 60 day after planting and chickpeas, while the spacing does not significantly affect all parameters. The treatment of spacing of 20 cm x 40 cm with a dose of fertilizer 10 t / ha has been sufficient to increase the yield of beans per plot (4.25 t / ha) higher than other treatments.